Design and Antischizophrenic Studies of 1,3-disubstituted Chalcone Derivatives: In-silico Molecular Docking Approach - Abdulqadir Okhayole Zubair; Suleiman Danladi; Umar Idris Ibrahim; Mahdiyu Kogi Jibril; Salim Ilyasu (Tropical Life Sciences Research, 2025)
Schizophrenia is a psychiatric disorder that affects a person’s ability to think, feel and behave clearly. The pathophysiology of the disease stems from the overexpression of dopamine neurotransmission and deficiency of glutamate activity at glutamate synapse in the brain. Considering the significant global burden of the disease, lack of complete efficacy using the current medications and variety of adverse effects associated with their use, and the huge opportunity created by Computer-Aided Drug Design, it is therefore important and possible to come up with drug leads that will have improved efficacy and reduced side effects. This research is thus aimed to design, evaluate the pharmacokinetic properties, and the in silico antischizophrenic activity of novel 1,3-disubstituted chalcones. Ten compounds were designed using ChemDraw Ultra 7.0 using similarity approach and their oral bioavailability was predicted using SwissADME, toxicity was predicted using PROTOX 3.0 and docking studies were carried out using AutoDock Vina through Chimera 1.11.2. The 10 designed compounds were predicted to have excellent oral bioavailability and lead-likeness properties, easy synthesisability and a relatively safer toxicity profile than the reference compound clozapine. The compounds were evaluated to have higher docking scores between –8.3 to –9.5 compared to clozapine with a docking score of -8.8 when docked against dopaminergic D2 receptor. In addition, the compounds have close binding scores (–6.0 to –6.6) compared to clozapine (–6.7) when docked against N-Methyl-D-aspartic Acid (NMDA) receptor, suggesting their use as potential antischizophrenic agents.